SOCIETY AND SOCIAL MEDIA: PUBLIC OPINION ON THE PHENOMENON OF USTAD SOLMED AS A SYMBOL OF “RICH AND RELIGION” - Sari, Fitri Meliya; Nurdin, Hanifah; Situmeang, Marini Kristina; Putri, Sukma Ari Ragil; Syifaurrahmah, Syifaurrahmah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study analyzes the